1997
DOI: 10.1007/bf02273936
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols of the fruits of some varieties of pomegranate growing in Uzbekistan

Abstract: Continuing a search for promising tannide-bearing plants [1][2][3] with the aim of using them to produce drugs and highquahty tanning agents, we have investigated the polyphenols of the fruits of several varieties of Punica granatum (Kazaki, Shirindona, Aehchikdona, Kai, Kizil) growing on the territory of Uzbekistan, By a method developed earlier [1], from the peel of pomegranates of the Kazaki variety we isolated ethyl acetate and butanol fractions of the total polyphenols (2.9% and 6.8%, respectively, of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The anthocyanin profile in arils of mid-July fruit contained peaks corresponding to Dp3,5, Cy3,5 and Cy3. Arils from mid-December fruit contained in addition to the latter also Dp3 and Pg3, resembling the anthocyanin profile reported for pomegranates grown in the Mediterranean, Iran and Uzbekistan. ,,, …”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The anthocyanin profile in arils of mid-July fruit contained peaks corresponding to Dp3,5, Cy3,5 and Cy3. Arils from mid-December fruit contained in addition to the latter also Dp3 and Pg3, resembling the anthocyanin profile reported for pomegranates grown in the Mediterranean, Iran and Uzbekistan. ,,, …”
Section: Resultssupporting
confidence: 71%
“…Arils from mid-December fruit contained in addition to the latter also Dp3 and Pg3, resembling the anthocyanin profile reported for pomegranates grown in the Mediterranean, Iran and Uzbekistan. 12,13,19,20 The concentrations of the individual anthocyanins were evaluated from the corresponding chromatograms' peak areas and the relevant calibration curve, as previously described. Total anthocyanin level was calculated by their summation.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Extracts of pomegranate peel have been shown to suppress cell growth in various cancer cell lines. 42 , 44 , 45 Anti-carcinogenic features of various mixtures of the phytochemicals in pomegranate were evaluated before. 46 Tang et al 47 discovered that punicalagin inhibits the β-catenin signaling pathway, hence possessing chemopreventive and chemotherapeutic properties against human cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate polyphenols include flavonoids (flavonols, flavanols and anthocyanins) (Santagati et al, 1984;Hernandez et al, 1999;van Elswijk, 2004), tannins (proanthocyanidins) and hydrolysable tannins (ellagitannins and gallotannins) (Tanaka et al, 1986;Satomi et al, 1993;Hussein et al, 1997;Mavlyanov et al, 1997). The flowers also contain triterpenoids (Batta & Rangaswami, 1973;Huang et al, 2005), and alkaloids were identified from the bark of tree and root (Neuhofer et al, 1993).…”
Section: Research Articlementioning
confidence: 99%